The effectiveness of music therapy in improving behavioral symptoms among children with autism spectrum disorders: a systematic review and meta-analysis - Xiuyan Gao; Guangjun Xu; Ningning Fu; Qi Ben; Lin Wang; Xiumei Bu (Frontiers in Psychiatry)
ObjectivesThis comprehensive review and meta-analysis aimed to thoroughly identify the effectiveness of music therapy (MT) in improving behavioral symptoms in children with autism spectrum disorders (ASD) by analyzing the data from all relevant randomized controlled trials (RCTs) related to this field.MethodsFrom inception until September 18, 2024, PubMed, Web of Science, the Cochrane Library, SinoMed, and Embase were searched. Two reviewers extracted the data separately, and any controversies between the authors’ assessments were resolved by conversation or speaking with another author. The behavioral symptoms scale score before and after the intervention was taken from the included trials and used to reflect the therapeutic effect of music therapy in children with autism.Results2607 records across all retrieved databases were discovered, thirteen of which were included in a meta-analysis with 1160 participants. According to the meta-analysis, children with autism showed a substantial improvement in their behavior symptoms when receiving music treatment (standardized mean difference [SMD] = -0.66, 95% confidence interval [CI]: -0.93 to -0.39, p < 0.001). With I2 = 78% and P < 0.001, we did discover a medium level of heterogeneity among the included studies.ConclusionsMT has a positive impact on improving behavioral symptoms in children with autism. However, given the significant heterogeneity and limitations in this study, RCTs with rigorous methodological quality are still required to confirm the curative benefits of MT in autistic children precisely.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024597939.